2020
DOI: 10.1177/2158244019898800
|View full text |Cite
|
Sign up to set email alerts
|

Do Gender, Discipline, and Mental Rotation Influence Orientation on “You-Are-Here” Maps

Abstract: A common challenge people encounter in unfamiliar cities is finding their way using static maps. In the present study, we analyzed the relationship of a person’s mental rotation ability, college educational specialization (e.g., Architecture, Fine Arts, Psychology, and Business Studies), and sex with personal orientation when using “you-are-here” maps. We recruited a sample of 547 individuals, undergraduates who were tasked with orientation maps placed in different positions (e.g., 0º, 90º, and 180º). All thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Individuals high in the ability to rotate mental imagery obtained more correct graph-comprehension responses than individuals low in the ability to rotate mental imagery. These results coincided with those obtained in studies analyzing the influence of imagery rotation in complex figures and mathematical problem-solving (Campos & Campos-Juanatey, 2019a;Reingewertz, 2013;Sanchez & Wiley, 2014;Van Garderen, 2006), the interpretation of maps (Campos & Campos-Juanatey, 2019a;Campos-Juanatey & Campos, 2019), and the ability to orient oneself on you-are-here maps. Moreover, the results of this study agreed with other studies analyzing the comprehension of both macroeconomic (Reingewertz, 2013) and microeconomic graphs (Marangos & Alley, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Individuals high in the ability to rotate mental imagery obtained more correct graph-comprehension responses than individuals low in the ability to rotate mental imagery. These results coincided with those obtained in studies analyzing the influence of imagery rotation in complex figures and mathematical problem-solving (Campos & Campos-Juanatey, 2019a;Reingewertz, 2013;Sanchez & Wiley, 2014;Van Garderen, 2006), the interpretation of maps (Campos & Campos-Juanatey, 2019a;Campos-Juanatey & Campos, 2019), and the ability to orient oneself on you-are-here maps. Moreover, the results of this study agreed with other studies analyzing the comprehension of both macroeconomic (Reingewertz, 2013) and microeconomic graphs (Marangos & Alley, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Visual artists, such as painters and sculptors, mainly use object imagery, whereas scientists, physicist, engineers, and architects primarily use spatial imagery (Campos & Fuentes, 2016;Kozhevnikov et al, 2005;Kozhevnikov et al, 2010;Motes et al, 2008;Pérez-Fabello et al, 2016;Pérez-Fabello et al, 2018). Image rotation is linked to spatial tasks involving movement, the interpretation of complex graphs, and mathematical problem-solving (Campos & Campos-Juanatey, 2019a;Reingewertz, 2013;Sanchez & Wiley, 2014;Van Garderen, 2006;Zhao & Della Sala, 2018). Campos and Campos-Juanatey (2019a) found that individuals with a high ability to rotate mental imagery obtained more correct responses in understanding you-are-here maps than individuals with low ability to rotate mental imagery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation